Amphibian asemblage of Bubu Permanent Forest Reserve, Perak, Peninsular Malaysia - Ibrahim, J.; Wong, J.; Mohd. Fazlin, M.S.; Fatan, H.Y.; Siti Hadijah, Y.; Norhaslinda, S. (Penerbit Universiti Kebangsaan Malaysia, 2011)
A brief study of the amphibian fauna of Bubu Permanent Forest Reserve, Perak, which constitutes the southernmost part of the Bintang Hijau Forest Reserve, was carried out from 18 to 21 December 2006 to determine the diversity and density estimate of amphibian species in the area. Field parties comprising seven persons searched and collected amphibians from a small stream, the Dal River, in Compartments 6 and 7 of the Bubu Permanent Forest Reserve, from 2000 hrs to 2300 hrs for three consecutive nights. A total of 79 individual frogs from 13 species in five families were recorded. The five most abundant species were Hyalarana nicobariensis, H. labialis, Pedostibes hosii, Phrynoides aspera and Amolops larutensis. Six other species were considered rare, namely, Limnonectes doriae, H. picturata, Odorrana hosii, Polypedates leucomystax and Rhacophorus bimaculatus. Preliminary analysis of the data showed that the estimated populations of H. nicobariensis, H. labialis and P. hosii are 23, 13 and 10 individuals per 100 meters of river length, respectively. Due to the brief nature of the study, and the small area covered, the number of species is considered relatively moderate. More than 95% of frogs collected are forest species that require clean and pollution-free habitats to survive. This shows that the Dal River is a pristine river flowing from the Gunung Bubu range. It originated from a virgin jungle, hence it has clear waters with a minimum amount of pollution and disturbance. We hope that the relevant authorities will preserve it as it is for the benefit of future generations and more importantly, for the continued survival of the amphibian fauna.